2020
DOI: 10.2196/16978
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spin in the Abstracts of Systematic Reviews and Meta-Analyses Focused on the Treatment of Acne Vulgaris: Cross-Sectional Analysis

Abstract: Background Spin is the misrepresentation of study findings, which may positively or negatively influence the reader’s interpretation of the results. Little is known regarding the prevalence of spin in abstracts of systematic reviews, specifically systematic reviews pertaining to the management and treatment of acne vulgaris. Objective The primary objective of this study was to characterize and determine the frequency of the most severe forms of spin in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 27 publications
7
27
0
Order By: Relevance
“…In the field of dermatology, Motosko et al [35] concluded that spin strategies were common in clinical trials covering topical treatments for photoaged skin. Recently, Ottwell et al [36] found spin in 31% of abstracts of systematic reviews focused on acne interventions. While a number of factors may account for this sizable difference, one possible explanation may be the different treatment approaches for acne versus AD [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of dermatology, Motosko et al [35] concluded that spin strategies were common in clinical trials covering topical treatments for photoaged skin. Recently, Ottwell et al [36] found spin in 31% of abstracts of systematic reviews focused on acne interventions. While a number of factors may account for this sizable difference, one possible explanation may be the different treatment approaches for acne versus AD [37].…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of our study include: (1) encouraging reproducibility of our study by making our protocol, search strategy, data extraction form, data, analysis scripts, and other resources available online via the Open Science Framework [22]; (2) performing screening and data extraction in a masked, duplicate fashion to minimize human error and bias, which is currently recommended by the Cochrane Collaboration [29]; and (3) allowing an independent group to verify our data, ensuring that our results are reproducible. The limitations of our study include: (1) subjectivity inherent in classifying spin during data extraction; (2) the cross-sectional design of this study limits the generalizability of our study results; (3) studies not available in English were excluded which limits our sample size; (4) the ability of our search strings to identify all systematic reviews on AD treatments and interventions; (5) since all the industry-funded studies contained spin, we could not evaluate the statistical significance between the industry-funding variable and spin; and (6) in our protocol we prespecified the possibility of a binary logistic regression and calculated a power analysis to determine sample size based on the results of a previous spin study [36]. Our final sample size of 113 was not powered to perform the multivariable logistic regression and therefore is a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Spin has been defined by Yavchitz et al 11 as 'a specific way of reporting, intentional or not, to highlight that the beneficial effect of the experimental treatment in terms of efficacy or safety is greater than that shown by the results'. Several studies have shown spin to be present in the abstracts of randomized controlled trials [12][13][14][15][16] ; however, comparatively few studies have looked at spin in the abstracts of systematic reviews 17,18 . Thus, the objective of this study is to assess the abstracts of systematic reviews regarding smoking cessation treatments for the presence of spin, and to evaluate whether particular study characteristics are associated with spin.…”
Section: Introductionmentioning
confidence: 99%
“…This study was performed in accordance with a previously written protocol available publicly on Open Science Framework (OSF) [19]. A search of PubMed and EMBASE, which incorporates MEDLINE, was performed on September 2, 2019.…”
Section: Publication Searchmentioning
confidence: 99%